Antioxidant capacity of value-added sandwich cookie creams based on red palm olein during storage - Mohamad Shah, N. K.; Sanny, M.; Ab Karim, N. A.; Kuppan, K.; Yahaya, N. A.; Mat Yusoff, M. (Consejo Superior de Investigaciones Científicas, 2023)
Red palm olein (RPOL) is naturally rich in antioxidants, yet changes in its antioxidant capacity during storage were uncertain, which limited the application of RPOL in fat-based food products. Therefore, this study incorporated shortenings composed of 0, 5, and 10% (w/w) RPOL into sandwich cookie creams of SCC-0, SCC-5, and SCC-10, respectively, and determined their antioxidant capacity during storage for six months at 20, 30, and 35 ºC. Both SCC-5 and SCC-10 exhibited higher carotene, tocopherol, tocotrienol, and total phenolic content (TPC) than that of SCC-0, yet all SCCs were comparable in their free fatty acid (FFA) and UV-total oxidation values. After six months, the SCCs exhibited low TPC and FFA, yet were high in DPPH scavenging activity. At 20 and 30 ºC, both SCC-5 and SCC-10 oxidized more slowly than that of SCC-0. These findings proved the antioxidant capacity of RPOL, which delayed oxidation reactions in the SCCs during storage.